Quality of working life and engagement in an evolving hospitality subsector: the case of hostels - Lehtinen, Tiia Annika (2014)
Hostels’ competitiveness relies strongly on the unique genuineness in service and thus counts on employees that are actively creating a social and welcoming environment, while at the same time caring about the company. However, the trend of hostels becoming more upscale might compromise the genuineness in service as the employees face pressure to become more normative. Retaining employees that care about the company (e.g. positive voice behavior) implies engaging them and also providing high quality of working life, particularly with a room to be creative. Taking these variables as central in dealing with the current trends in the hostel industry, we tested a model with a sample of 98 employees from Lisbon hostels, in which engagement mediates the relation between quality of working life and voice behavior. Findings support the hypothesized model showing that one of the work engagement dimensions (dedication) fully mediates the relation between quality of working life (creativity) and voice.